1997
DOI: 10.1097/00000542-199711000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-sparing Effects of a Low-dose Infusion of Naloxone in Patient-administered Morphine Sulfate 

Abstract: Naloxone is effective in preventing PCA opioid-related side effects. Naloxone infusion at 0.25 microg x kg(-1) x h(-1) not only attenuates these side effects but appears to reduce postoperative (beyond 4-8 h) opioid requirements. This dosing regimen can be prepared with 400 microg naloxone in 1,000 ml crystalloid given in 24 h to a patient weighing 70 kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
170
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(179 citation statements)
references
References 19 publications
7
170
0
2
Order By: Relevance
“…Naloxone was chosen from the other opioid antagonists available for multiple reasons: availability, cost, safety profile in breast feeding and potential intrinsic analgesic properties when given in low doses [16,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naloxone was chosen from the other opioid antagonists available for multiple reasons: availability, cost, safety profile in breast feeding and potential intrinsic analgesic properties when given in low doses [16,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…(420 lg.day )1 in a 70-kg subject) has been shown to reduce pruritus significantly and possibly decrease analgesic requirements in patients undergoing abdominal hysterectomy who received intravenous morphine patient-controlled analgesia [16]. Doses of > 1 lg.kg…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug has been reported to reduce the incidence of opioid-induced pruritus among adult patients receiving morphine by postoperative PCA, from 55% with placebo to 25% with naloxone. 27 No respiratory depression was observed with naloxone, and no differences in respiratory rate, sedation scores, blood pressure, heart rate, or oxygen saturation between naloxone and placebo groups were reported. 27 In children, naloxone "piggy-backed" into patients' morphine PCA infusions reduced the incidence of pruritus from 77% in the placebo group to 20% in the naloxone group.…”
Section: Introductionmentioning
confidence: 91%
“…27 No respiratory depression was observed with naloxone, and no differences in respiratory rate, sedation scores, blood pressure, heart rate, or oxygen saturation between naloxone and placebo groups were reported. 27 In children, naloxone "piggy-backed" into patients' morphine PCA infusions reduced the incidence of pruritus from 77% in the placebo group to 20% in the naloxone group. 9 In an underpowered pilot study (n = 16 patients) examining co-infusion of morphine with low-dose (0.25 µg/kg per hour) or high-dose (1 µg/kg per hour) naloxone, trends suggested that the high-dose group had a lower incidence of pruritus than the low-dose group.…”
Section: Introductionmentioning
confidence: 91%